Diseño e implementación de una maquina CNC para la elaboración de prototipos de circuitos impresos y diseños en 3D para uso de estudiantes de CIEYT - Alvarado Hidalgo, Adrian Alexander (2023)
Three-dimensional printers (three-dimensional) and CNC (Computer Numerical Control) machines are recent innovations in modern industry, enabling engineers to design mechanical parts previously impossible. The following final project aims to make two design prototypes; a 3D printer that designs three-dimensional figures up to 10 cm in height and a CNC machine that designs printed circuits of a single layer of copper. The design prototypes, such as the 3D printer and CNC were made with easily available materials, for which Nema 17 motors were used to facilitate the Cartesian movement of the 3D printer and CNC, a Hot-end extruder model MK8 that helps the absorption of PLA filament (polylactic acid), in addition to being accompanied by a graphic display that allows interaction with the G-CODE file (G-code) that will control the printing of the piece in the third dimension; and a drill or Dremel that allows to make the tracks or engraving inside the copper plate. This will allow us to have very favorable results with professional or industrial printers, obtaining 3D printed objects in our hands and plates with copper tracks with very acceptable percentages. Since these devices are not so common in our homes or offices due to their high price, it was proposed to build a 3D printer and CNC economic with the possibility of creating three-dimensional models and printed circuit boards (PCB). The project will also serve as a platform for promoting small businesses that operate in this field in Loja. Keywords: CNC machine, printed circuits, 3D printer, PCB, PLA.